2022
DOI: 10.1155/2022/4326437
|View full text |Cite
|
Sign up to set email alerts
|

Visualization of Railway Transportation Engineering Management Using BIM Technology under the Application of Internet of Things Edge Computing

Abstract: In the past, railway line planning usually required engineers to design based on their own experience after a series of field visits, leading to heavy workload and low efficiency. Moreover, operation and maintenance management is more complicated due to an abundance of railway station equipment. Based on the above problems, this paper first puts forward the railway transportation line planning and design method based on Building Information Modeling (BIM) technology. Besides, LocaSpace Viewer realizes the thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…The real innovation lies in the creation of a plug-in that allows extrapolation directly from the design program to the computational model, which then simulates the proposed transport structure in a real context. The project of using BIM in conjunction with the Internet of Things (IoT) is described in [41]. It is an efficient planning and design of rail transport lines with 3D visualization and scenic modeling of the railway environment.…”
Section: Bim In Railway Transportmentioning
confidence: 99%
“…The real innovation lies in the creation of a plug-in that allows extrapolation directly from the design program to the computational model, which then simulates the proposed transport structure in a real context. The project of using BIM in conjunction with the Internet of Things (IoT) is described in [41]. It is an efficient planning and design of rail transport lines with 3D visualization and scenic modeling of the railway environment.…”
Section: Bim In Railway Transportmentioning
confidence: 99%
“…The study was carried out concerning indicators such as clarity of design solutions, number of conflicts, quality of work, control/predictability of costs, requests for changes, etc. The results showed that BIM resulted in 38.5% quality improvement, 38.5% conflict reduction, 61.5% clearer design, 23.1% fewer changes and 30.8% more accurate cost estimates [19,20]. However, the management of I-BIM is affected by considerable constraints linked to the single geometry that makes up the various infrastructure elements, hence the lack of standardization of products [21].…”
Section: Theoretical Backgroundmentioning
confidence: 99%